PRAKTIK MANAJEMEN SDM, WORKING ATMOSPHERE, KEPUASAN KERJA DAN INTENTION TO STAY PADA TENAGA KESEHATAN DI KLINIK KECANTIKAN : A Case Study of Healthcare Workers in Aesthetic Beauty Clinics - Pebria, Refriani; Syaebani, Muhammad Irfan (Jurnal Ilmiah Ekonomi Dan Bisnis, 2023)
In recent years, many doctors and other healthcare workers choose to work in the aesthetic beauty industry. Based on data from Statista, the beauty and body care market in Indonesia in 2021 will reach 7.46 billion USD and is expected to grow to increase to 7.25% in 2023. Therefore, it is important to identify the factors that can influence healthcare workers can work in a beauty clinic. This study used a quantitative research method by distributing questionnaires using a 5-point Likert scale. Using the SEM (Structural Equation Modelling) technique, a sample of 237 healthcare workers who worked in beauty clinics was obtained. The findings showed that HR management practices and working atmosphere positively and significantly affect job satisfaction and ultimately increase their intention to stay. Thus, job satisfaction plays a role in mediating the effect of human resource management practices on the intention to stay. This study implies that healthcare organizations should pay more attention to human resource management practices and working atmosphere to increase the job satisfaction of healthcare workers thereby influencing the intention to stay. In addition, HR management practices and an efficient work environment can improve the quality of health services and minimize treatment errors.